1994
DOI: 10.1111/j.1476-5381.1994.tb14798.x
|View full text |Cite
|
Sign up to set email alerts
|

ETA receptor‐mediated responses to endothelin‐1 and big endothelin‐1 in the rat kidney

Abstract: 1 Renal clearance experiments were conducted in anaesthetized Sprague-Dawley rats to determine the effect of the ETA receptor antagonist, BQ-123, on the renal haemodynamic response to endothelin-1 (ET-1) and its precursor, big endothelin-1 (big ET-1) at doses that produce an equivalent degree of renal vasoconstriction.2 Infusion of either big ET-1 at 100 pmol kg-min' or ET-1 at 12pmolkg-'min'1 for 60min produced almost identical decreases in renal blood flow (RBF) and glomerular filtration rate (GFR). Big ET-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
36
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 20 publications
9
36
0
Order By: Relevance
“…Thus, ET did not seem to have the same predilection for the renal vasculature as Ang II. This lack of effect of the ET antagonists on basal renal tone is consistent with previous studies in rat kidneys 17,18 that also suggest that the balance between Ang II and NO/PGs is more important in the maintenance of basal renal vascular tone than ET. However, although ET blockade did not alter RBF significantly when Ang II was present, its effect was striking when Ang II was blocked (group 3); RBF increased dramatically (by 46%).…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Asupporting
confidence: 91%
“…Thus, ET did not seem to have the same predilection for the renal vasculature as Ang II. This lack of effect of the ET antagonists on basal renal tone is consistent with previous studies in rat kidneys 17,18 that also suggest that the balance between Ang II and NO/PGs is more important in the maintenance of basal renal vascular tone than ET. However, although ET blockade did not alter RBF significantly when Ang II was present, its effect was striking when Ang II was blocked (group 3); RBF increased dramatically (by 46%).…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Asupporting
confidence: 91%
“…Although indications for slight differences in the susceptibility of the two ET B receptor locations to different ET B antagonists have been reported (26, 28), the similarity of the responses to ET B agonists S6C and IRL-1620 in the present study speaks against a major difference in sensitivity of endothelial and smooth muscle ET B receptors, at least at the employed doses of ET B agonists. Finally, it has been suggested that the relative influence of the dilator effect of endothelial ETB receptors is smaller or absent at lower doses of ET-1 (35,36), possibly due to a higher affinity of endothelial than smooth muscle ET B receptors for ET-1. However, binding curves for ET-1 are typically monophasic, including renal microvascular tissue (15,17), thus giving no indication for different affinities of endothelial and smooth muscle receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Specific vascular beds, vessel size, species (22,33), hydration status (34), or strength of stimulation (34) may play a role. Anesthesia does not seem to be a major factor for either the finding of predominant ET Amediated constriction (7,8,23,36) or predominant ET Bmediated renal vasoconstriction (25,36). However, an important contributing factor seems to be the experimental strategy employed.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Even if some of the constrictor effects of endothelin intrarenally are mediated via ETB receptors, ETA-selective compounds have already proved effective not only in antagonizing the haemodynamic responses in rats to infused ET-1 and big ET-1 (Pollock & Opgenorth, 1994) but also in limiting tissue necrosis and biochemical changes in at least two rat models; a cyclosporine-induced model of nephrotoxicity (Fogo et al, 1992) and a model of chronic renal failure associated with reduced renal mass (Benigni et al, 1993). This is despite reports that, in rats at least, some part of renal vasoconstriction is ETB-mediated.…”
Section: Discussionmentioning
confidence: 99%